Biotechnological Importance of Torulaspora delbrueckii: From the Obscurity to the Spotlight - Fernandes, Ticiana (2021)
Torulaspora delbrueckii has attracted interest in recent years, especially due to its biotechnological potential, arising from its flavor- and aroma-enhancing properties when used in wine, beer or bread dough fermentation, as well as from its remarkable resistance to osmotic and freezing stresses. In the present review, genomic, biochemical, and phenotypic features of T. delbrueckii are described, comparing them with other species, particularly with the biotechnologically well-established yeast, Saccharomyces cerevisiae. We conclude about the aspects that make this yeast a promising biotechnological model to be exploited in a wide range of industries, particularly in wine and bakery. A phylogenetic analysis was also performed, using the core proteome of T. delbrueckii, to compare the number of homologous proteins relative to the most closely related species, understanding the phylogenetic placement of this species with robust support. Lastly, the genetic tools available for T. delbrueckii improvement are discussed, focusing on adaptive laboratorial evolution and its potential.